CONSTRUCTION OF AN EXPRESSION VECTOR BASED ON pCDNA3.1(+) EXPRESSING JEMBRANA DISEASE VRIUS ENV-TM SUBUNIT GENE IN EUKARYOTIC SYSTEM - Asmarani Kusumawati; Joannes Sri Widada; Basuki Hidayat (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2004)
.